Health Benefits of Micronutrients (Vitamins and Minerals) and their Associated Deficiency Diseases: A Systematic Review - Godswill, Awuchi Godswill; Somtochukwu, Igwe Victory; Ikechukwu, Amagwula O; Kate, Echeta Chinelo (International Journal of Food Sciences, 2020)
The research focused on the benefits of micronutrients (vitamins and minerals) and their associated deficiency diseases and health complications. Micronutrients are essential elements required by human and other organisms in varying quantities throughout life to coordinate a range of physiological functions for health maintenance. For human nutrition, micronutrients are required in amounts generally below 100 milligrams per day, while macronutrients are required in gram amounts daily. Vitamins and minerals are essential micronutrients. Essential nutrients cannot be synthesized in humans, either at all or may be in insufficient amounts, and therefore must be obtained by the diet. Vitamin C can be synthesized by some organisms but not by others; it is not a vitamin in the first instance but is in the second. In humans there are 13 vitamins: 9 water-soluble (8 B vitamins and vitamin C) and 4 fat-soluble (A, D, E, and K). Vitamins A and D can amass in the body, which may result in dangerous hypervitaminosis. Anti-vitamins inhibit the actions or absorption of vitamins; avidin inhibits biotin absorption, although it is deactivated by cooking; Pyrithiamine inhibits enzymes that use vitamin B1. The four key structural elements in human body (oxygen, hydrogen, carbon, and nitrogen) by weight, are often not included in the lists of major nutrient minerals (nitrogen is a "mineral" for plants, as it is often included in fertilizers). These four key elements compose around 96% of the weight of human body, and the major minerals (macrominerals) and minor minerals (trace elements) compose the remaining percent. The five major minerals in the the human body are calcium, phosphorus, potassium, sodium, and magnesium (macrominerals or macroelements). The trace elements with specific biochemical function in human body are iodine, sulfur, zinc, iron, chlorine, cobalt, copper, manganese, molybdenum, and selenium. Calcium makes up 920 to 1200 g of body weight (about 1.5% of body weight) of an adult, with 99% of it contained in the bones and teeth. Phosphorus occurs in amounts of around 2/3 of calcium, and makes up approximately 1% of an individual's body weight. The other macroelements (potassium, sodium, magnesium, chlorine, and sulfur) make up only around 0.85% of the body weight